Epidemiology, genetic diversity and evolution of pigeon circovirus - Rongsheng Zhu; Lingzhi Luo; Ziqi Shi; Yun Chen; Jin Xu; Guoxin Li; Lingxue Yu; Jin Cui (Poultry Science)
With the global prevalence of pigeon racing, pigeon infections with Pigeon circovirus (PiCV) have been reported across the world. PiCV-infected pigeons are susceptible to subsequent infections and exhibit a range of symptoms including weight loss, lethargy, anorexia, respiratory distress and diarrhea, which exerts a huge impact on the pigeon industry. However, there is currently a lack of epidemiological data on PiCV infection in pigeons. Therefore, the aim of this study was to gain a comprehensive understanding of the prevalence, genetic variations, and evolutionary dynamics of PiCV within pigeon populations. In this study, we collected 28 samples from four cities in China to assess the prevalence of PiCV. The results showed that the positive rate was 92.86%, which indicated that PiCV was widespread in Chinese pigeon flocks. Meanwhile, whole genome sequences of PiCV were obtained for partial positive samples. The results showed that there were 12 different clades of PiCV, and the samples collected in this study have been classified as types 1, 4, 6, and 11. The results of the PiCV genome analysis indicate a high incidence of recombination events. Further analysis of the encoded Cap protein at the gene and protein level revealed a high degree of variation in the Cap protein. The amino acids at positions 30-120 of the Cap protein exhibited the greatest frequency of variation. Meanwhile, we found that amino acid sequences 140-180 were relatively conserved, which was related to the immunogenicity of the circovirus Cap protein. The results of the antigenicity analysis demonstrated that amino acid sequences 140-180 exhibited strong antigenicity, indicating the potential of cap to serve as a candidate protein in the production of a PiCV vaccine. The present study provided epidemiological information on PiCV, which promises to facilitate the development of effective control measures to prevent its transmission.